Ribonucleases - Nicholson, Allen W. (Nucleic Acids and Molecular Biology., 2011)
Ribonucleases are a ubiquitous and functionally diverse group of enzymes that have a common ability to cleave RNA. Either through scission of internal phosphodiesters, or removal of nucleotides from RNA 5' or 3' ends, ribonucleases perform essential roles in gene expression and regulation, genome replication and maintenance, host defense, stress response, and viral strategies of infection. Ribonucleases have also served as highly informative models to understand virtually every aspect of biomolecular structure and function. The fifteen chapters in this volume are written by recognized researchers in the field, and provide in-depth analyses of the major ribonuclease families. Particular focus is given to the relation of ribonuclease structure and mechanism to biological function, as well as ribonuclease dysfunction in certain disease states. Other topics include the evolutionary genetics and functional diversification of ribonucleases, engineered ribonucleases as anti-cancer agents, the mechanisms of action of artificial ribonucleases, and ribonucleases as models to understand protein folding and stability. This volume should serve as an essential reference for a broad range of researchers and educators with interests in RNA metabolism, enzymology, and gene regulation.